2020
DOI: 10.3389/fmed.2020.515506
|View full text |Cite
|
Sign up to set email alerts
|

Glycated Hemoglobin < 6.5% Is Associated With Uroseptic Shock in Diabetic Patients With Urinary Tract Infection

Abstract: This study aimed to compare the clinical characteristics and treatment outcomes of diabetic and non-diabetic individuals with urinary tract infection (UTI) and determine whether glycated hemoglobin (HbA1c) levels &lt;6. 5% leads to uroseptic shock in diabetic individuals. We retrospectively collected and analyzed the clinical data of 1,363 individuals with UTIs in Taiwan from January 2006 to January 2018. Of the 345 diabetic individuals, 61 (17.7%) developed uroseptic shock. Diabetic patients who developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…was ~2-fold more common as a uropathogen in diabetic individuals compared to nondiabetics ( P = 0.011), although there was no significant difference in the number of diabetic and nondiabetic individuals from whom UPEC, Proteus spp., Pseudomonas spp., and Enterococcus spp. were isolated as causative uropathogen [ 30 ]; (ii) a study from Argentina reported that ~7% individuals with GBS-UTI were diabetic [ 43 ]; (iii) in a prospective study of diabetics with culture positive UTI diagnosis ( N = 252), compared to subjects with good glycemic control (Hb A1C = 5.4% ± 0.5, N = 55), those with poor glycemic control (Hb A1C = 8.3% ± 1.5; N = 197) showed a 1.1-fold and 1.25-fold increase in the detection of UPEC and K. pneumoniae , respectively [ 44 ]; (iv) in a study from a French hospital (DM = 72; no DM = 227), DM increased the odds of polymicrobial ( E. faecalis , E. coli , and P. aeruginosa ) bacteriuria (OR adjusted for age and sex = 2.0; P = 0.04) [ 45 ]; and (iv) in pregnant women with pre-gestational DM (DM = 150; no DM = 294), diabetes significantly increased risk of bacteriuria caused by GBS (OR = 2.47) [ 46 ]. Whether the DM increases susceptibility to pathogens with specific virulence features is not examined extensively, although in a study, the presence of DM was not correlated with the recovery of hypermucoviscous K. pneumoniae from UTI patients [ 47 ].…”
Section: The Etiology Of Urinary Colonization In Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…was ~2-fold more common as a uropathogen in diabetic individuals compared to nondiabetics ( P = 0.011), although there was no significant difference in the number of diabetic and nondiabetic individuals from whom UPEC, Proteus spp., Pseudomonas spp., and Enterococcus spp. were isolated as causative uropathogen [ 30 ]; (ii) a study from Argentina reported that ~7% individuals with GBS-UTI were diabetic [ 43 ]; (iii) in a prospective study of diabetics with culture positive UTI diagnosis ( N = 252), compared to subjects with good glycemic control (Hb A1C = 5.4% ± 0.5, N = 55), those with poor glycemic control (Hb A1C = 8.3% ± 1.5; N = 197) showed a 1.1-fold and 1.25-fold increase in the detection of UPEC and K. pneumoniae , respectively [ 44 ]; (iv) in a study from a French hospital (DM = 72; no DM = 227), DM increased the odds of polymicrobial ( E. faecalis , E. coli , and P. aeruginosa ) bacteriuria (OR adjusted for age and sex = 2.0; P = 0.04) [ 45 ]; and (iv) in pregnant women with pre-gestational DM (DM = 150; no DM = 294), diabetes significantly increased risk of bacteriuria caused by GBS (OR = 2.47) [ 46 ]. Whether the DM increases susceptibility to pathogens with specific virulence features is not examined extensively, although in a study, the presence of DM was not correlated with the recovery of hypermucoviscous K. pneumoniae from UTI patients [ 47 ].…”
Section: The Etiology Of Urinary Colonization In Diabetesmentioning
confidence: 99%
“…In summary, these observations indicate a positive correlation between poor glycemic control and increasing risk of community- and hospital-acquired UTI. Interestingly, poor glycemic control does not appear to be a significant risk factor UTI progression into urosepsis [ 30 , 57 ].…”
Section: Epidemiological and Laboratory Studies Examining Hyperglycem...mentioning
confidence: 99%